2000
DOI: 10.1002/(sici)1097-0231(20000430)14:8<669::aid-rcm932>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ion mode and matrix additives in the identification of bacteria by intact cell mass spectrometry

Abstract: Protocols for the identification of bacterial cells by intact cell matrix-assisted laser desorption/ionisation time-of-flight mass spectrometry (ICM-TOFMS) are presented. A mass range of 500 to 10,000 m/z is used. The use of formic acid and the crown ether 1, 4, 7, 10, 13, 16-hexaoxacyclooctadecane (18-crown-6) is described. Crown ether is useful for removing metal ion adducts, which degrade spectral purity, and formic acid promotes positive ions, improves spectral signal, and, hence, increases identification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…6 are for E. coli removed from the agar surface 50 h past inoculation and analyzed in both positive‐ and negative‐ion mode. It has previously been reported that spectral information in the mass range of 600–2000 Da was greater in the positive mode for Enterococcus durans 25. Generally, the two acquisition modes are not complimentary in regards to either the qualitative appearance of the spectra or the overall peak intensities 26.…”
Section: Resultsmentioning
confidence: 95%
“…6 are for E. coli removed from the agar surface 50 h past inoculation and analyzed in both positive‐ and negative‐ion mode. It has previously been reported that spectral information in the mass range of 600–2000 Da was greater in the positive mode for Enterococcus durans 25. Generally, the two acquisition modes are not complimentary in regards to either the qualitative appearance of the spectra or the overall peak intensities 26.…”
Section: Resultsmentioning
confidence: 95%
“…Reproducibility of MALDI-TOF MS spectra is an important concern that has been addressed in a number of studies ( Gantt et al , 1999 ; Saenz et al , 1999 ; Evason et al , 2000 ; Jarman et al , 2000 ; Fenselau & Demirev, 2001 ; Valentine et al , 2005 ; Wunschel et al , 2005a , b ). In the present study, different MALDI preparations were initially tested using ATCC 700294 and varying solvents, matrices, plating techniques, and mass ranges.…”
Section: Discussionmentioning
confidence: 99%
“…For spotting, two different techniques were tested during preliminary experiments: the smear method and extraction using ethanol/formic acid. The direct colony technique (the smear method) was chosen for testing as several other studies reported this method as the most reproducible deposition technique . Ethanol/formic acid extraction is recommended for robust species and complicated samples .…”
Section: Resultsmentioning
confidence: 99%